Thyrotoxic Periodic Paralysis - Abdelrahim, Hisham Mohamed; M.Saeed, Amel Kamel; Elmansor, Rasha Elamin Ahmed (Gezira Journal of Health Sciences; Vol 15 No 2 (2019), 2019)
Periodic paralysis (PP) is a muscle disease in the family of diseases called channelopathies, manifested by episodes of painless muscle weakness. PP is classified as hypokalemic or hyperkalemic according to level of potassium (K⁺). Most cases of PP are hereditary, but acquired cases of hypokalemic PP have been described in association with hyperthyroidism. We report a case of 48 years old female who presented to ER with one day history of sudden onset of bilateral lower limbs weakness. She gave history of transient episode of bilateral leg weakness one week earlier, recovered spontaneously. She is known case of DM for eight years but has no family history of muscle disorders. Her examination at time of presentation, showed – in addition to the lower limbs weakness-clinical features of thyrotoxicosis. According to her clinical presentation, laboratory findings and the evident data of known association of hypokalemic periodic paralysis (PP) and thyrotoxicosis, the patient was diagnosed as hyperthyroidism with hypokalemic periodic paralysis. The patient responded very well to emergency management of hypokalemia as well as the treatment of thytotoxicosis. Thyrotoxic periodic paralysis (TPP) is a rare but potentially serious complication of thyrotoxicosis resulting in temporary but severe muscle weakness, Prompt recognition of the problem allows for proper short- and long-term management of this condition.